2021
DOI: 10.3389/fpsyt.2021.546801
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in Mood Disorders: From Physiology to Pathophysiology and to Treatment

Abstract: Mitochondria are cellular organelles involved in several biological processes, especially in energy production. Several studies have found a relationship between mitochondrial dysfunction and mood disorders, such as major depressive disorder and bipolar disorder. Impairments in energy production are found in these disorders together with higher levels of oxidative stress. Recently, many agents capable of enhancing antioxidant defenses or mitochondrial functioning have been studied for the treatment of mood dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 371 publications
(544 reference statements)
3
66
0
Order By: Relevance
“…The dysfunctional mitochondrial hypothesis is one of the current hypotheses that attempt to explain the origin of mood disorders. Many studies have confirmed that mood stabilizers affect mitochondrial functions, even though the exact mechanism or localization of action is unknown [ 347 ].…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The dysfunctional mitochondrial hypothesis is one of the current hypotheses that attempt to explain the origin of mood disorders. Many studies have confirmed that mood stabilizers affect mitochondrial functions, even though the exact mechanism or localization of action is unknown [ 347 ].…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Mitochondria are cellular organelles involved in energy production and several other biological processes, such as regulating oxidative stress and apoptosis. A relationship between mitochondrial dysfunction, characterised by impairments in energy production and increased oxidative stress and depression, has been reported in a wide range of studies on cell cultures, animal models, and clinical research [ 146 149 ]. Consequently, interest in treatments that target mitochondria dysfunction is on the rise.…”
Section: Curcumin’s Potential Antidepressant Mechanisms Of Actionmentioning
confidence: 99%
“…The dysfunctional mitochondrial hypothesis is one of current hypotheses attempts to explain the origin of mood disorders. Many studies have confirmed that mood stabilizers affect mitochondrial functions, even though the exact mechanism or localization of action is unknown [314].…”
Section: Bipolar Disordermentioning
confidence: 99%